Comparative, cross-sectional study of the format, content and timing of medication safety letters issued in Canada, the USA and the UK. Issue 10 (8th October 2018) - Bjerre, Lise M; Parlow, Simon; de Launay, David; Hogel, Matthew; Black, Cody D; Mattison, Donald R; Grimshaw, Jeremy M; Watson, Margaret C
Abstract : Objectives: To assess consistency in the format and content, and overlap of subject and timing, of medication safety letters issued by regulatory health authorities to healthcare providers in Canada, the USA and the UK. Design: A cross-sectional study comparing medication safety letters issued for the purpose of alerting healthcare providers to newly identified medication problems associated with medications already on the market. Setting: Online databases operated by Health Canada, the US Food and Drug Administration and the UK Medicines and Healthcare products Regulatory Agency were searched to select medication safety letters issued between 1 January 2010 and 31 December 2014. Format, content and timing of each medication safety letter were assessed using an abstraction tool comprising 21 characteristics deemed relevant by consensus of the research team. Main outcome measures: Main outcome measures included, first, characteristics (format and content) of medication safety letters and second, overlap of subject and release date across countries. Results: Of 330 medication safety letters identified, 227 dealt with unique issues relating to medications available in all three countries. Of these 227 letters, 21 (9%) medication problems were the subject of letters released in all three countries; 40 (18%) in two countries and 166 (73%) in only one country. Only 13 (62%) of the 21 letters issued in all three countries were released within 6 months of each other. Conclusions: Significant discrepancies in both the subject and timing of medication safety letters issued by health authorities in three countries (Canada, the USA and the UK) where medical practice is otherwise comparable, raising questions about why, how and when medication problems are identified and communicated to healthcare providers by the authorities. More rapid communication of medication problems and better alignment between authorities could enhance patient safety.